Neoproterozoic kimberlite and lamproite magmatism of the Man Craton, Liberia, from a common sub-lithospheric source - Njabulo Ndimande; Geoffrey H. Howarth; Andrea Giuliani; Philip E. Janney; Petrus le Roux; Marcel Guillong; Quentin Charbonnier; Stephen E. Haggerty (Mineralogy and Petrology, 2025)
It has been proposed that, rather than the lithosphere, cratonic lamproites may be derived from convecting mantle sources like those of kimberlites, but with extensive subsequent melt modification via melt-rock reaction with metasomatized, phlogopite-rich sub-continental lithospheric mantle (SCLM). Here we explore this model using samples from kimberlite (Camp Alpha) and olivine lamproite (Weasua) localities in Liberia, West Africa. U–Pb dating of perovskite, performed using in-situ Pb isotope compositions of coexisting (low U/Pb) mica, provides broadly coeval Neoproterozoic ages for Camp Alpha (762 ± 9 Ma) and Weasua (779 ± 6 Ma and 754 ± 7 Ma), indicating emplacement during break-up of the supercontinent Rodinia. The mineralogy and mica compositions along with bulk-rock geochemistry of Camp Alpha kimberlites are consistent with derivation from a sub-lithospheric mantle source. The Weasua lamproite contains perovskite with trace element concentrations (e.g., Sr < 3000 µg/g), trace element ratios (e.g., Th/U, Th/Nb, and La/Nb), and 87 Sr/ 86 Sr values (0.7029 to 0.7030) that overlap those of perovskite in the Camp Alpha kimberlites ( 87 Sr/ 86 Sr = 0.7028 ± 0.0002). These data are also similar to those of perovskite in worldwide Neoproterozoic to Cambrian-aged kimberlites but distinct from typical cratonic lamproites, which exhibit perovskite with high Sr contents (> 4000 µg/g) and Sr isotope signatures typical of the enriched lithospheric mantle (bulk-rock 87 Sr/ 86 Sr i generally > 0.7050). A possible petrogenetic model for the Weasua lamproites entails derivation from a sub-lithospheric source similar to that of the Camp Alpha kimberlites with mineralogical, and hence major-element, variations between these two proximal localities driven by variable assimilation of heterogeneous SCLM material.

Petrogenesis of the Tuli Basin high-Ti picrites and basalts, Karoo CFB, southern Africa: Classification, stratigraphy, emplacement, and mantle source heterogeneity - Geoffrey H. Howarth; Julian S. Marsh; Andy R. Duncan; Chris Harris; Jussi S. Heinonen; Stephen H. Richardson; Anton le Roex; Richard W. Carlson; Robert E. Zartman (Lithos, 2023)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

A role for artificial night-time lighting in long-term changes in populations of 100 widespread macro-moths in UK and Ireland: a citizen-science study - John Fawcett Wilson; David Baker; Janet Cheney; Mike Cook; Martin Ellis; Roger Freestone; David Gardner; Graham Geen; Robin Hemming; Don Hodgers; Stephen Howarth; Ade Jupp; et al. (Journal of Insect Conservation, 2018)

The secondary origin of diamonds: multi-modal radiation tomography of diamondiferous mantle eclogites - Geoffrey H. Howarth; Nikolay V. Sobolev; John F. Pernet-Fisher; Peter H. Barry; Dayakar Penumadu; Stephen Puplampu; Richard A. Ketcham; Jessica A. Maisano; Dawn Taylor; Lawrence A. Taylor (International Geology Review, 2014)

Limitations of integrated assessment models of climate change - Frank Ackerman; Stephen J. DeCanio; Richard B. Howarth; Kristen Sheeran (Climatic Change, 2009)